GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 8310 species occurrences available in GBIF matching the query: TaxonKey: 6 Country: Niger. The dataset includes 8310 records from 61 constituent datasets: 106 records from Database Schema for UC Davis [Herbarium Labels]. 1 records from MfN - Fossil plants (Paleophytic). 1 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 6 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 381 records from Naturalis Biodiversity Center (NL) - Botany Wageningen. 10 records from Paleobiology Database. 10 records from iNaturalist research-grade observations. 11 records from Geographically tagged INSDC sequences. 247 records from Herbarium Senckenbergianum (FR). 9 records from Tiroler Landesmuseum Ferdinandeum. 9 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 9 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 11 records from Collection Paleobotanique de l'Universite Paris 6. 1 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 1 records from Bryophyte herbarium, Trondheim (TRH). 14 records from Phanerogamic Botanical Collections (S). 526 records from Naturalis Biodiversity Center (NL) - Botany. 28 records from Herbarium of The New York Botanical Garden. 9 records from Herbarium of Taiwan Forestry Research Institute. 14 records from Royal Botanic Garden Edinburgh Herbarium (E). 5 records from naturgucker. 19 records from UA Herbarium. 2 records from Australia's Virtual Herbarium. 302 records from United States National Plant Germplasm System Collection. 120 records from EURISCO, The European Genetic Resources Search Catalogue. 49 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 13 records from PRECIS. 26 records from Missouri Botanical Garden. 3 records from Botany (UPS). 2 records from IICT Herbário LISC. 4 records from Naturalis Biodiversity Center (NL) - Botany Utrecht. 2 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 744 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from CZE National PGR Inventory. 10 records from Carnet en Ligne. 3 records from USU-UTC Specimen Database. 4 records from Herbier CNRST/INERA. 30 records from Mosses (S). 14 records from NMNH occurrence DwC-A. 1 records from Vascular Plant Herbarium, Oslo (O). 32 records from Herbarium Berolinense. 600 records from SINGER Coordinator. 54 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 11 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 19 records from Harvard University Herbaria. 3587 records from The System-wide Information Network for Genetic Resources (SINGER). 9 records from University of Ghana - Ghana Herbarium. 9 records from HBGBryophyta - Herbarium Hamburgense. 65 records from Natural History Museum (London) Collection Specimens. 44 records from Herbier du Bénin. 318 records from Nationaal Herbarium Nederland. 612 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 18 records from Royal Museum of Central Africa - Metafro-Infosys - Prelude. 2 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 1 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 8 records from Geneva Herbarium – General Collection (G). 111 records from West-, Central- and East African Plants Databases. 11 records from Natural History Museum, Vienna - Herbarium W. 37 records from Cryptogamy collection (PC) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2 records from CAS Botany (BOT). 2 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM).
Keywords: GBIF; biodiversity; species occurrences